(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2022)
There are different forms of coastal erosion management: do nothing, accommodation (adaptation or relocation), and protection (soft and hard solutions; Williams et al., 2018). On the coast of the province of Buenos Aires, Argentina, several of the above techniques have been used, i.e. armoring, moderation and restoration, especially in the city of Mar del Plata (General Pueyrredón country). The beaches in front of the central part of the city have a large number of breakwaters. Those structures, which were built without an adequate design, favored the migration of erosive processes downdrift, i.e. in the direction of the coastal sediment transport (south to north). Other protection works that were carried out are the beach nourishment projects that use sands extracted from different sources, both marine and continental. The most relevant work was carried out in 1998 with sand extracted from the sand shoal accumulated at the outlet of the port. The beaches located in the southern part of the city are almost natural and only in recent years a few protection structures, such as groins and rip-rap revetments of orthoquartzite rocks have been emplaced. Because of this, the southern area is preserving a high degree of landscape and sanitary quality for bathing purposes. The study area is located at the southern end of the General Pueyrredón country, within a protected area named Reserva Turística y Forestal Paseo Costanero Sur, which has an extension of 27 km from the Punta Mogotes lighthouse to the Las Brusquitas creek (Fig. 1c). The area has a great variety of landforms: pocket beaches, dune fields, tall cliffs, at places covered with fossil dunes, and rock platforms. A feature of oceanographic interest is the existence of a littoral cell in the Ensenada de Mogotes (northernmost part of the study area). These beaches are susceptible to storms, mainly approaching from the south, that causes coastline and cliff retreat, generating a risk for the neighborhoods and for the stability of the route 11 that runs on top of these cliffs. Likewise, this provincial route between the cities of Mar del Plata and Miramar, in the sector near the San Eduardo del Mar neighborhood, is affected by the migration of dunes under the action of winds blowing from WSW. It is often required the intervention of the municipality to rehabilitate the route. Such sands are usually not reintegrated to the coastal sediment budget, despite the fact that there have been carried out in recent years different studies recommend that for a sustainable management (Fig.1). The objective of the present work was to analyze the possible use of the sands accumulated by the wind on the Provincial Route 11 in the vicinity of the San Eduardo del Mar neighborhood to carry out artificial nourishments at the beaches belonging to the Reserva Turística y Forestal Paseo Costanero Sur, i.e. Playa Serena, Luna Roja, Chapadmalal and San Eduardo del Mar beaches (Fig.1). Beach nourishment is considered a soft protection solution consisting in the artificial fill of the beach using sand (“borrow sand”) from another site. The purpose is to increase the width of the backshore and thus to keep the toe of the cliffs away from the action of the waves. This method also provides recreational benefits by increasing the tourist capacity and, therefore, the associated economic value for local municipalities. The methodology used for this work was divided into two parts: on the one hand, a survey of the beaches was carried out by means of topographic profiles with an analog theodolite during low tide conditions to determine the beach width and slope. At the same time, four sediment samples were obtained from a depth of one centimeter (respect to the surface of the beach), and then sieved in laboratory to determine the average grain size and statistical parameters (Folk and Ward, 1957) using the Gradistat software (Blott and Pye, 2001). On the other hand, the suitability of natural and borrow sediments was checked by applying the James diagram (1975). Using the statistical parameters, the Overfill factors (Ra) value, which indicate the suitability (and therefore the probable behavior) of the borrow material respect to the native material, were calculated; and the Renourishment factor (Rj), which indicates how often the replenishment of the borrow material would be required (U.S. ACE, 1984). For the eolian sands of the dune field, the grain size data were obtained from previous sampling (García González et al., 2021). Table 1 summarizes the results of the beach profiles and grain-size parameters for each beach. In general, beach lengths range from 40 to 70 m, slopes from 3 % to 5 % and the grain sizes are quite varied, from fine sands to gravel sizes (2 phi to -2.5 phi). Applying the James (1975) diagram, it was found that the best combination was the one corresponding to the replenishment of Playa Serena. In other words, only 1.02 m³ of borrow material (i.e. sand from the mobile dunes) is needed to replenish 1 m³ of native sand in that beach, and it had to be replenished 0.14 times more often respect to the present material. The rest of the beaches gave interesting results: for Chapadmalal and San Eduardo del Mar beaches the Ra ratios were also small (Ra: 1.05 and 1.02, respectively and Rj: 1.5), while Luna Roja had the highest values (Ra: 5.0 and Rj: 2; Table 3). The results presented above allowed the following conclusions: • Comparing sediment compositions in the Ensenada de Mogotes fine sand sizes prevail (Playa Serena 2.5 phi) while the grain sizes become coarser and with a smaller selection (San Eduardo del Mar 0.5 phi) outside of the Ensenada. • According to the topographic profiles, the beaches farther away from the Ensenada present steeper slopes (i.e. 5 %, Luna Roja and San Eduardo del Mar) with biggest grain sizes. Chapadmalal beach is an exception because it is a bimodal beach related to a breakwater. • The diagrams of James showed that the aeolian sands of the San Eduardo del Mar dunes can be used as borrow sediment to nourish the beaches within the protected area Reserva Turística y Forestal Paseo Costanero Sur. • Results from the Ra and Rj diagrams allowed to state that borrow sand (obtained from mobile dunes) is especially to the Playa Serena sands (Ra 1.02 and Rj 0.14) and renourishments values are also suitable for the beaches of Chapadmalal and San Eduardo del Mar. • Considering the distance between the borrow area (the mobile dunes) and the beaches, San Eduardo del Mar and Chapadmalal are the most adequate to avoid large transportation costs, because the first one is located very close to dune field and the second one is only 5.3 km away.